1996
DOI: 10.1038/380252a0
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery in parkinsonian monkeys treated with GDNF

Abstract: Parkinson's disease results from the progressive degeneration of dopamine neurons that innervate the striatum. In rodents, glial-cell-line-derived neurotrophic factor (GDNF) stimulates an increase in midbrain dopamine levels, protects dopamine neurons from some neurotoxins, and maintains injured dopamine neurons. Here we extend the rodent studies to an animal closer to the human in brain organization and function, by evaluating the effects of GDNF injected intracerebrally in rhesus monkeys that have had the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
499
1
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 904 publications
(522 citation statements)
references
References 20 publications
19
499
1
3
Order By: Relevance
“…34 The presence of GDNF messenger RNA (mRNA) in the astrocytes of substantia nigra, 35,36 and the high sensitivity of DA neurons to this neurotrophin make GDNF a likely candidate for the yet unidentified VPA-induced, astrocytes-secreted neurotrophic substance. [37][38][39] To test this possibility, we used real-time PCR to quantify GDNF mRNA. Results showed that VPA treatment caused a time-dependent increase in GDNF mRNA levels in astroglial cultures.…”
Section: Resultsmentioning
confidence: 99%
“…34 The presence of GDNF messenger RNA (mRNA) in the astrocytes of substantia nigra, 35,36 and the high sensitivity of DA neurons to this neurotrophin make GDNF a likely candidate for the yet unidentified VPA-induced, astrocytes-secreted neurotrophic substance. [37][38][39] To test this possibility, we used real-time PCR to quantify GDNF mRNA. Results showed that VPA treatment caused a time-dependent increase in GDNF mRNA levels in astroglial cultures.…”
Section: Resultsmentioning
confidence: 99%
“…1 Although GDNF does not penetrate the brain from the blood, studies in Parkinsonian primates showed that direct infusion into the ventricles led to a reversal of symptoms. 2 Furthermore, a series of experiments in both monkeys and rats have shown that GDNF can prevent dopamine neuron cell loss and induce fiber sprouting in a wide range of different models of PD. 3 This led to a clinical trial where GDNF was administered via bolus injections directly into the ventricles of Parkinsonian patients.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Unlike the case with BDNF, however, there is also evidence for restoration of function of injured neurons by GDNF after toxic insults 33,36,40 although restorative actions are generally not as dramatic as the neuroprotective actions. 33 A series of influential studies from Gash, Gerhardt, and coworkers [41][42][43] have demonstrated GDNF-induced improvement in bradykinesia, rigidity, and postural instability in monkeys with stable MPTP-induced hemiparkinsonism. GDNF was effective when given by bolus or by constant infusion, and through three routes of administration: intranigral, intrastriatal, and intracerebroventricular (ICV).…”
Section: Gdnfmentioning
confidence: 99%
“…42,57 Intracerebroventricular injection of GDNF in the monkeys with MPTP-induced parkinsonism increased the number and size of dopaminergic neurons in the midbrain, as well as increasing dopamine levels, in both parkinsonian and normal monkeys. 41,58 This method of delivery of GDNF was not, however, successful in humans. It is extremely likely that in humans a protein trophic factor would not diffuse from ventricular ependyma to the putamen, which in the much larger human brain lies more than 1 cm away from the ventricles.…”
Section: Manipulating Trophic Factors For Therapeutic Benefitmentioning
confidence: 99%
See 1 more Smart Citation